The rupture process of the source of the 2016 Ecuador earthquake (Mw 7.8) - Jimenéz, César (2020)
The 2016 Ecuador earthquake (Mw 7.8), is part of the sequence of large earthquakes in Ecuador and Colombia: 1906 (8.4 to 8.8 Mw), 1942 (Mw 7.8), 1958 (Mw 7.7), 1979 (Mw 8.2), all these events with a focal mechanism of the thrust fault type. In this research, we have obtain the seismic source distribution (indicating the presence of 2 main asperities), from inversion of teleseismic signals, as well as the parameters of the seismic rupture process: focal mechanism that indicates a type of inverse fault (strike = 25°, dip = 12°, rake = 118°) for a focal depth of 23 km and the source time function indicating a composite event, the duration of the rupture process was around 70 s, assuming an average rupture velocity of 3.0 km/s. The seismic moment was calculated at 5.74x10{20} Nm, equivalent to a magnitude of Mw 7.8. The smallest asperity is located around the epicenter and the main asperity is located around the coastline to the south-east of the epicenter. The maximum dislocation or slip was 3.8 m. In this case, the vertical coseismic deformation pattern does not favor the generation of a large tsunami.